The evolution of medical genetics - Harper, Peter S., author.
1 online resource.
Keywords: "This informative new book presents an accessible account of the development of medical genetics over the past 70 years, one of the most important areas of 20th, and now 21st, century science and medicine. Based largely on the author's personal involvement and career as a leader in the field over the last half century, both in the UK and internationally, it also draws on his interest and involvement in documenting the history of medical genetics. Underpinning the content is a unique series of 100 recorded interviews undertaken by the author with key older workers in the field, the majority British, which has provided invaluable information going back to the very beginnings of human and medical genetics. Focusing principally on medically relevant areas of genetics rather than the underlying basic science and technological aspects, the book offers a fascinating insight for those working and training in the field of clinical or laboratory aspects of medical genetics and allied areas; it will also be of interest to historians of science and medicine and to workers in the social sciences who are increasingly attracted by the social and ethical challenges posed by modern medical genetics"--